EFL STUDENTS’ PERCEPTION OF MALL IN FOSTERING VOCABULARY MASTERY: A MIXED METHODS APPROACH - Ferdiansah, Deny; Indrayadi, Toni; Musdizal, Musdizal (Universitas Muhammadiyah Metro, 2025)
Technology plays a crucial role in helping students enhance their vocabulary mastery. A lack of attention to proper vocabulary learning during the teaching and learning process can pose challenges. Numerous studies have explored EFL students' perceptions of vocabulary development through technology. However, limited research has examined the influence of gender on students’ attitudes in this context. Therefore, this study aims to investigate EFL students’ attitudes toward English vocabulary enhancement concerning gender differences. An explanatory mixed-methods approach was employed, incorporating Davis’ (1993) questionnaire on technology integration in language learning and interviews. Quantitative data were gathered from 72 students and analyzed using descriptive statistical methods. Additionally, qualitative data were collected through semi-structured interviews with ten participants and examined using thematic analysis. The questionnaire findings indicated that students responded positively to the use and convenience of MALL, with no significant differences observed between male and female students. Moreover, interview results suggested that MALL facilitated vocabulary comprehension and mastery. These findings not only recommend the incorporation of more practical vocabulary learning media but also equip English lecturers with actionable insights to enhance student engagement in the learning process. This study also contributes to English pedagogy by emphasizing the importance of integrating technology into vocabulary learning.